Effectiveness of the seven-valent and thirteen-valent pneumococcal conjugate vaccines in England: The indirect cohort design, 2006–2018. Issue 32 (26th July 2019) - Andrews, Nick; Kent, Alison; Amin-Chowdhury, Zahin; Sheppard, Carmen; Fry, Norman; Ramsay, Mary; Ladhani, Shamez N.
Abstract: Background: The 7-valent pneumococcal conjugate vaccine (PCV7) was introduced into the UK childhood immunisation programme in 2006 and replaced with a 13-valent vaccine (PCV13) in 2010. Both vaccines led to rapid declines in vaccine-serotype invasive pneumococcal disease (IPD). Here, we assessed the long-term vaccine-effectiveness (VE) of both vaccines in England. Methods: Public Health England conducts enhanced national surveillance of IPD in England. VE against IPD was estimated using vaccine-serotype IPD cases and non-vaccine serotype IPD controls among vaccine-eligible children from September 2006 to June 2018 (the Broome method). Results: Vaccine history was available for 3421 IPD cases, including 1299 due to the additional PCV13 serotypes and the PCV13-related serotype 6C, 274 PCV7 serotypes and 1848 non-PCV13 serotypes. For the complete 2 + 1 schedule, both PCV7 and PCV13 showed high effectiveness against PCV7 serotypes with a combined VE of 92.0% (95%CI, 81.7–96.7). For the 2 + 1 schedule, PCV13 VE against the additional PCV13 serotypes plus 6C was 73.7% (31.1–89.9) compared to 90.0% (75.3 – 96.0) for PCV7 against PCV7 serotypes, although PCV13 VE increased to 84.8% (58.7–94.4) if serotype 3 was excluded; all 36 eligible serotype 3 IPD cases were fully-vaccinated with PCV13. Case numbers were low in older ages but there was evidence of waning, which was significant for serotype 19A for which there were sufficient numbers of cases for analysis. Conclusions: PCVs are highly effective in preventing vaccine-serotype IPD except for serotype 3 which has been increasing in incidence. Serotype 19A IPD has also persisted, likely due to a slightly lower VE and/or more rapid waning of protection.